VOC measurements during OASIS Barrow field intensive Spring 2009, Version 1.0 - Apel, E. (UCAR/NCAR - Earth Observing Laboratory, 2012)
A measurement intensive campaign was carried out in Barrow, Alaska in spring 2009 as part of the Ocean-Atmosphere-Sea-Ice-Snowpack program. This dataset contains Volatile Organic Compounds (VOCs) measured using the Trace Organic Gas Analyzer (TOGA) during the campaign.